A method for preparing a composite catalytic material for degrading microplastics in water
The preparation of lanthanum cobaltate-biochar composite catalytic material through coprecipitation-pyrolysis method has solved the problem of poor effect of existing catalytic materials when degrading microplastics in water, achieved efficient degradation and convenient recycling, improved processing efficiency and reduced costs.
Patent Information
- Application Number
- CN202411243330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The existing catalytic materials have poor results when degrading microplastics in water, and have problems such as poor catalyst activity, agglomeration of nanometal particles and difficulty in solid-liquid separation.
The lanthanum cobaltate-biochar composite catalytic material was prepared by coprecipitation-pyrolysis method, and the lanthanum cobaltate was coated on the surface of the biochar material through in-situ synthesis method to form a composite catalytic material with the ability to efficiently activate permonosulphate.
It realizes efficient degradation of microplastics in water, improves processing efficiency, and facilitates solid-liquid separation and recycling through magnetic properties, reducing costs.
Smart Images

Figure CN119281338B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a method for preparing a composite catalytic material for degrading microplastics in water. The composite material is a lanthanum cobaltate-biochar composite catalytic material. Background Art
[0002] Microplastics generally refer to plastic fragments, particles and fibers with a particle size of less than 5 mm. Microplastics have been detected to be widely present in water bodies. Due to their small size, large specific surface area and difficulty in degradation, they pose a potential threat to aquatic life and human health. As an emerging pollutant, microplastics not only contain toxic substances themselves, but also absorb other pollutants such as heavy metals, antibiotics, and persistent organic matter, forming more complex and more biologically toxic composite pollutants. Therefore, the pollution control technology of microplastics in water environments has become a new focus in the environmental field.
[0003] At present, the treatment methods for microplastics in water mainly include physical methods, biological methods, and advanced oxidation methods. Physical methods such as coagulation and filtration cannot fundamentally degrade microplastics and cannot achieve complete removal of microplastics. Biological methods have the advantages of low cost and environmental friendliness, but the biodegradation of microplastics has problems such as long cycle and low efficiency. Advanced oxidation methods have a good degradation effect on microplastics and are considered to be a very promising way to treat microplastics. Among them, permonosulfate can produce sulfate radicals after being activated by catalytic materials, which has the advantages of thorough degradation, fast reaction rate, and wide range of water quality applications. However, when the current metal-based, carbon-based and other catalytic materials are used as monosulfate activators, there are problems such as poor catalyst activity, agglomeration of nano-metal particles, and difficulty in solid-liquid separation in water treatment. Therefore, it is necessary to develop catalytic materials that can effectively activate permonosulfate to achieve its efficient degradation of microplastics in water.
[0004] Biomass raw materials are one of the main factors that determine the physical and chemical properties of biochar. Biomass is usually composed of lignin, cellulose and hemicellulose. Cellulose and hemicellulose are more likely to produce volatile gases such as H2, CO2, and CH4 during the carbonization process. The pyrolysis of lignin mainly produces residual biochar. The proportions of lignin, cellulose and hemicellulose in different biomasses are different, and the pore structure of biochar after pyrolysis is different.
[0005] In addition, it is reported that although some walnut shells are processed and utilized as agricultural and sideline products, a large amount of walnut shells are still not properly treated as waste, and some areas even burn them as fuel, which seriously threatens the quality of the air environment. Since walnut shell charcoal contains more lignin, the yield of the biochar produced after pyrolysis is higher, and the surface has a large number of active sites. Therefore, the present invention uses walnut shells as carriers to prepare lanthanum cobaltate-biochar and use it for microplastic degradation, providing a theoretical reference for the sustainable utilization of agricultural residues and the large-scale preparation of cheap and efficient biomass-based catalysts. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a composite catalytic material for degrading microplastics in water, so as to solve the problem that the existing catalytic materials have poor degradation effect on microplastics.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A method for preparing a composite catalytic material for degrading microplastics in water comprises the following steps:
[0009] S1, washing, drying, crushing and sieving the walnut shells in sequence;
[0010] Preferably, when the walnut shells are cleaned, deionized water is used to clean the walnut shells 2 to 3 times.
[0011] Preferably, during the drying process, the cleaned walnut shells are placed in a constant temperature drying oven and dried at 60-80° C. for 6-8 h.
[0012] Preferably, when the walnut shell powder is sieved, the particle size is set to 60 mesh.
[0013] S2, adding the sieved walnut shell powder to a mixed solution containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid, stirring and mixing at room temperature, adjusting the pH value of the mixed solution with ammonia water until lanthanum cobaltate is precipitated on the surface of the walnut shell powder particles, and then heating the mixed solution in a water bath until the water in the mixed solution is completely evaporated;
[0014] The concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O, and citric acid in the mixed solution were 30~40mmol / L, 30~40 mmol / L, and 35 mmol / L, respectively;
[0015] Preferably, the volume ratio of the added mass of the walnut shell powder to the mixed solution is 30 g / L to 60 g / L.
[0016] Preferably, the stirring and mixing time at room temperature is 20 to 60 minutes.
[0017] Preferably, the pH of the mixed solution is adjusted to 7-9 using ammonia water, and then the mixed solution is stirred for 20-40 minutes until there is no obvious change in the color of the mixed solution, and it is judged that the lanthanum cobaltate is completely precipitated. The pH value has a significant effect on the phase composition and micromorphology of lanthanum cobaltate. When the pH of the precursor solution is adjusted to about 5, precipitation begins to occur. When the pH value of the precursor solution is too low, no obvious precipitation is produced, the product lanthanum cobaltate crystals are not fully developed, and obvious agglomeration will occur, and the particle size is uneven; in a solution with a pH of 7-9, lanthanum cobaltate has the highest crystallinity, and the product is a fluffy and porous honeycomb structure; when the pH is too high, the product is mainly amorphous, and the structure tends to be dense.
[0018] S3. The mixture obtained by coprecipitation is dried and ground in sequence, and then pyrolyzed to obtain a lanthanum cobaltate-biochar-based composite catalytic material.
[0019] Preferably, the heating rate during pyrolysis treatment is 3-5°C / min, the pyrolysis treatment temperature is 600-800°C, and the pyrolysis treatment time is 2-4 h. The pyrolysis temperature is related to the phase composition and morphology of the product. Within 600-800°C, the crystallinity of lanthanum cobaltate is the best. When the pyrolysis temperature is too low, the crystallization of lanthanum cobaltate is incomplete; when the temperature is too high, the original biochar pore structure on the surface of the product collapses, the active sites are reduced, and the energy consumption is too high.
[0020] Preferably, during the pyrolysis treatment, high-purity nitrogen is used as the protective gas.
[0021] The present invention also provides a lanthanum cobaltate-biochar-based composite catalytic material prepared by the method.
[0022] The present invention also provides the use of the lanthanum cobaltate-biochar-based composite catalytic material in catalytic degradation of microplastics in water.
[0023] Compared with the prior art, the present invention has at least the following beneficial effects:
[0024] (1) In the above scheme, the lanthanum cobaltate-biochar composite catalytic material is prepared by coprecipitation-pyrolysis method, and the lanthanum cobaltate is coated on the surface of the biochar material by an in-situ growth synthesis method, which can avoid the phenomenon of lanthanum cobaltate agglomeration and cobalt dissolution. At the same time, the lanthanum cobaltate-biochar composite catalytic material obtained has strong magnetism, which is conducive to rapid solid-liquid separation and easy recovery when used in water treatment.
[0025] (2) The lanthanum cobalt oxide precipitate formed by co-precipitation is an oxide with a typical perovskite structure and has the ability to efficiently activate permonosulfate; the biochar formed by pyrolysis has the advantages of high conductivity, porous structure, and large specific surface area, and can act as a catalyst as well as a carrier of lanthanum cobalt oxide, which helps Co2+ / Co 3+ The catalytic activity of the composite catalytic material can be enhanced by the efficient synergistic "adsorption-oxidation" of the composite catalytic material. It can achieve efficient activation of permonosulfate and rapid degradation of microplastics in water, greatly improving the treatment efficiency.
[0026] (3) The preparation method of the lanthanum cobaltate-biochar composite catalytic material provided by the present invention is simple, mainly through adjusting the pH value of the mixed solution to carry out coprecipitation reaction, and subsequent pyrolysis treatment, does not require complex material preparation equipment, has low requirements for laboratory preparation, and does not produce polluting by-products throughout the process, which conforms to the concept of green preparation. At the same time, the raw material for preparing biochar is solid waste walnut shells, which reduces the cost of catalytic materials and realizes the resource utilization of solid waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0028] Figure 1 This is the XRD characterization diagram of the lanthanum cobaltate-biochar composite catalytic material in Example 2;
[0029] Figure 2 This is a SEM image of the lanthanum cobaltate-biochar composite catalytic material in Example 2;
[0030] Figure 3 The degradation rate of microplastics by the prepared composite catalytic material used in the examples and comparative examples. DETAILED DESCRIPTION
[0031] The following is a detailed description of the preparation method of the lanthanum cobaltate-biochar composite catalytic material for degrading microplastics in water provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods for some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0032] It should be noted that the references to "one embodiment", "embodiment", "exemplary embodiments", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).
[0033] Lanthanum cobalt oxide is an oxide with a typical perovskite structure and has the ability to efficiently activate permonosulfate. Biochar materials have excellent electronic properties and can act as a catalyst and a carrier of metal compounds, playing a role in promoting catalysis and improving overall catalytic activity. Both transition metals and carbon-based materials can achieve permonosulfate activation. Combining the two activation methods can improve their ability to remove organic pollutants. Lanthanum cobalt oxide, as a perovskite-type oxide, has the advantages of stable structure and high redox activity. It can be used as an effective permonosulfate activator and plays a major activation role. Walnut shell-based biochar has the advantages of high conductivity, porous structure, and large specific surface area. It can be used as a carrier of lanthanum cobalt oxide to reduce its agglomeration.
[0034] The present invention provides a method for preparing a composite catalytic material for degrading microplastics in water. Based on the preparation method, a lanthanum cobaltate-biochar composite catalytic material is obtained to improve Co 3+ / Co 2+ The redox cycling ability enables the synergistic and efficient activation of permonosulfate by cobalt lanthanate and biochar, which can achieve efficient catalytic degradation of microplastics in water.
[0035] The preparation steps of lanthanum cobaltate-biochar composite catalytic material are as follows:
[0036] Step 1. Wash the walnut shell raw material with deionized water 2-3 times to remove soluble impurities, and then place it in a constant temperature drying oven at 60-80 ° C for 6-8 hours. The dried walnut shell is crushed with a stainless steel crusher and passed through a 60-mesh sieve, and then put into a plastic sealed self-sealing bag for standby use;
[0037] Step 2, take 3-6g of sieved walnut shells and add them into 100mL of a mixed solution containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid, the concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid are 30-40mmol / L, 30-40 mmol / L and 35 mmol / L respectively. After stirring at room temperature for 30 min, adjust the pH value of the mixed solution to 7-9 with ammonia water until lanthanum cobaltate is precipitated on the surface of the walnut shell powder particles, and heat the mixed solution in a water bath until the water in the mixed solution is completely evaporated;
[0038] Step 3. Place the material obtained after water evaporation in a vacuum tube furnace for pyrolysis. The pyrolysis rate is 5 ℃ / min, the temperature is 600-800 ℃, and the pyrolysis time is 2-4 h. During the whole process, high-purity nitrogen is passed through the furnace to maintain a vacuum state. After the pyrolysis is completed, it is cooled to room temperature to obtain a lanthanum cobaltate-biochar-based composite catalytic material.
[0039] In the preparation method of the present invention, lanthanum cobaltate is loaded on the surface of the biochar material by in-situ precipitation to construct a lanthanum cobaltate-biochar composite catalytic material. The catalytic material prepared based on this method can effectively alleviate the agglomeration of lanthanum cobaltate and the dissolution of cobalt, with low cost and simple preparation process. The composite catalytic material obtained by the preparation method has an excellent function of activating permonosulfate, can achieve efficient degradation of microplastics in water, and is easy to use. At the same time, the lanthanum cobaltate-biochar composite catalytic material obtained has strong magnetism, which is conducive to rapid solid-liquid separation and convenient recovery.
[0040] The following is explained in conjunction with specific embodiments, and the following embodiments are preferred embodiments:
[0041] Example 1
[0042] (1) The walnut shell raw material was washed with deionized water for 2 to 3 times to remove soluble impurities, and then placed in a constant temperature drying oven at 60 ° C for 8 h. The dried walnut shell was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0043] (2) Take 3 g of sieved walnut shells and add them into 100 mL of a mixed solution A containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid. The concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid are 30 mmol / L, 30 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, the pH value of the mixed solution is adjusted to 7.0 with ammonia water until lanthanum cobaltate is precipitated on the surface of the walnut shell powder particles. The mixed solution is heated in a water bath until the water in the mixed solution is completely evaporated.
[0044] (3) The material obtained after the evaporation of water was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 600 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a lanthanum cobalt oxide-biochar-based composite catalytic material.
[0045] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by permonosulfate activated by lanthanum cobaltate-biochar-based composite catalytic material. It was calculated that under the catalytic action of lanthanum cobaltate-biochar-based composite catalytic material, the degradation rate of microplastics was 70.66% after 30 hours of reaction.
[0046] Example 2
[0047] (1) The walnut shell raw material was washed with deionized water for 2 to 3 times to remove soluble impurities, and then placed in a constant temperature drying oven at 70 ° C for 7 h. The dried walnut shell was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0048] (2) 4.5 g of sieved walnut shells were added to 100 mL of a mixed solution containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid. The concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid were 35 mmol / L, 35 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, the pH value of the mixed solution was adjusted to 8.0 with ammonia water until lanthanum cobaltate was precipitated on the surface of the walnut shell powder particles. The mixed solution was heated in a water bath until the water in the mixed solution was completely evaporated.
[0049] (3) The material obtained after the evaporation of water was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 700 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a lanthanum cobalt oxide-biochar-based composite catalytic material.
[0050] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by activated permonosulfate by lanthanum cobaltate-biochar-based composite catalytic material. It was calculated that under the catalytic action of lanthanum cobaltate-biochar-based composite catalytic material, the degradation rate of microplastics after 30 hours of reaction was 71.41%.
[0051] Figure 1 This is the XRD characterization diagram of the lanthanum cobaltate-biochar composite catalytic material in Example 2, indicating that the main components of the product are lanthanum cobaltate and carbon, and the crystallinity of lanthanum cobaltate is very high. Figure 2 This is a SEM image of the lanthanum cobaltate-biochar composite catalytic material in Example 2, with a magnification of 1660 times, indicating that in the obtained composite catalytic material, irregular lanthanum cobaltate nanoparticles are loaded on the porous biochar surface and have abundant active sites. The above test results provide a basis for demonstrating the excellent catalytic performance of the composite catalytic material.
[0052] Example 3
[0053] (1) The walnut shell raw material was washed with deionized water for 2 to 3 times to remove soluble impurities, and then placed in a constant temperature drying oven at 80 °C for 7 h. The dried walnut shell was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0054] (2) Take 6 g of sieved walnut shells and add them into 100 mL of a mixed solution containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid. The concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid are 40 mmol / L, 40 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, the pH value of the mixed solution is adjusted to 8.5 with ammonia water until lanthanum cobaltate is precipitated on the surface of the walnut shell powder particles. The mixed solution is heated in a water bath until the water in the mixed solution is completely evaporated.
[0055] (3) The material obtained after the evaporation of water was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 800 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a lanthanum cobalt oxide-biochar-based composite catalytic material.
[0056] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by activated permonosulfate by lanthanum cobaltate-biochar-based composite catalytic material. It was calculated that under the catalytic action of lanthanum cobaltate-biochar-based composite catalytic material, the degradation rate of microplastics after 30 hours of reaction was 72.00%.
[0057] Comparative Example 1
[0058] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 2 mM potassium permonosulfate was added to the suspension for oxidative degradation. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed, and the weight loss rate of the microplastics was used to represent the degradation rate of the microplastics in the water by the action of permonosulfate alone. It was calculated that the degradation rate of microplastics was only 8.22% after 30 hours of reaction under the oxidation of permonosulfate alone.
[0059] Comparative Example 2
[0060] (1) The wheat straw raw material was washed with deionized water for 2-3 times to remove soluble impurities, and then dried in a constant temperature drying oven at 60 °C for 8 h. The dried wheat straw was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0061] (2) Take 3 g of sieved wheat straw and add it to 100 mL of mixed solution A containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid. The concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid are 30 mmol / L, 30 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, the pH value of the mixed solution is adjusted to 7.0 with ammonia water until lanthanum cobaltate is precipitated on the surface of the wheat straw powder particles. The mixed solution is heated in a water bath until the water in the mixed solution is completely evaporated.
[0062] (3) The material obtained after water evaporation was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 600 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a lanthanum cobaltate-biochar-based (wheat straw) composite catalytic material.
[0063] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by activated permonosulfate of lanthanum cobaltate-biochar-based (wheat straw) composite catalytic material. It was calculated that under the catalytic action of lanthanum cobaltate-biochar-based (wheat straw) composite catalytic material, the degradation rate of microplastics after 30 hours of reaction was 62.11%.
[0064] Comparative Example 3
[0065] (1) The walnut shell raw material was washed with deionized water for 2 to 3 times to remove soluble impurities, and then placed in a constant temperature drying oven at 60 ° C for 8 h. The dried walnut shell was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0066] (2) Take 3 g of sieved walnut shells and add them into 100 mL of mixed solution A containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and citric acid. The concentrations of Co(NO3)2·6H2O, Fe(NO3)3·9H2O and citric acid are 30 mmol / L, 30 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, adjust the pH value of the mixed solution to 7.0 with ammonia water and heat it in a water bath until the water in the mixed solution is completely evaporated.
[0067] (3) The material obtained after water evaporation was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 600 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a cobalt-iron-biochar-based composite catalytic material.
[0068] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by permonosulfate activated by cobalt-iron-biochar-based composite catalytic materials. It was calculated that under the catalytic action of cobalt-iron-biochar-based composite catalytic materials, the degradation rate of microplastics after 30 hours of reaction was 47.82%.
[0069] Comparative Example 4
[0070] (1) The walnut shell raw material was washed with deionized water for 2 to 3 times to remove soluble impurities, and then placed in a constant temperature drying oven at 60 ° C for 8 h. The dried walnut shell was crushed with a stainless steel crusher, passed through a 60-mesh sieve, and placed in a plastic sealed ziplock bag for later use;
[0071] (2) Take 3 g of sieved walnut shells and add them into 100 mL of mixed solution A containing Co(NO3)2·6H2O, Fe(NO3)3·9H2O and citric acid. The concentrations of Co(NO3)2·6H2O, Fe(NO3)3·9H2O and citric acid are 30 mmol / L, 30 mmol / L and 35 mmol / L, respectively. After stirring at room temperature for 30 min, adjust the pH value of the mixed solution to 7.0 with ammonia water and heat it in a water bath until the water in the mixed solution is completely evaporated.
[0072] (3) The material obtained after water evaporation was placed in a vacuum tube furnace for pyrolysis at a pyrolysis rate of 5 °C / min, a temperature of 300 °C, and a pyrolysis time of 4 h. High-purity nitrogen was passed through the furnace to maintain a vacuum state during the entire process. After the pyrolysis was completed, it was cooled to room temperature to obtain a lanthanum cobalt oxide-biochar-based composite catalytic material.
[0073] 0.5 g of polystyrene microplastics (PS) were dispersed in 100 mL of deionized water and ultrasonicated for 10 minutes to completely disperse them; then 0.25 g of composite catalytic material was added to the suspension, and 2 mM potassium permonosulfate was added to trigger the degradation reaction. After 30 hours of reaction, the remaining solid matter in the water was collected by centrifugation and weighed; the weight loss rate of microplastics was used to represent the degradation rate of microplastics in water by activated permonosulfate by lanthanum cobaltate-biochar-based composite catalytic material. It was calculated that under the catalytic action of lanthanum cobaltate-biochar-based composite catalytic material, the degradation rate of microplastics after 30 hours of reaction was 15.88%.
[0074] The degradation rates of microplastics in water activated by potassium permonosulfate of the lanthanum cobaltate-biochar composite catalytic materials of Examples 1, 2, and 3 of the present invention were compared with those of Comparative Examples 1-4, and a microplastic degradation rate bar graph was drawn. The results are as follows: Figure 3 shown.
[0075] Figure 3 It is shown that through the performance test experiments of the composite catalytic materials in Examples 1, 2, and 3, i.e., the degradation experiment of microplastics in water treated with potassium permonosulfate activated by lanthanum cobaltate-biochar composite catalytic materials, it can be seen that the composite catalytic materials prepared by the method of the present invention have a degradation rate of more than 70% for microplastics (PS) within 30 hours, showing excellent catalytic degradation performance.
[0076] From the experimental results of microplastic degradation in comparative example 1, it can be seen that under the condition of permonosulfate alone, the degradation rate of microplastics within 30 hours is only 8.22%, and the removal effect of microplastics is very low.
[0077] Compared with the examples, comparative example 2 replaces walnut shells with wheat straw, comparative example 3 replaces lanthanum cobaltate with cobalt iron, and the pyrolysis temperature of comparative example 4 is too low. The above comparative examples show that if the raw materials or reaction conditions are changed, the degradation effect will be significantly affected. It is further verified that the lanthanum cobaltate-biochar composite catalytic material prepared by the present invention exhibits excellent performance in activating potassium permonosulfate to degrade microplastics in water.
[0078] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. Application of lanthanum cobaltate-biochar-based composite catalytic material in catalytic degradation of microplastics in water, characterized in that: The preparation method of the composite catalytic material comprises the following steps: S1, washing, drying, crushing and sieving the walnut shells in sequence; S2, adding the sieved walnut shell powder to a mixed solution containing Co(NO3)2·6H2O, La(NO3)3·6H2O and citric acid, stirring and mixing at room temperature, adjusting the pH value of the mixed solution with ammonia water until lanthanum cobaltate is precipitated on the surface of the walnut shell powder particles, and then heating the mixed solution in a water bath until the water in the mixed solution is completely evaporated; S3. The mixture obtained by coprecipitation is dried and ground in sequence, and then pyrolyzed to obtain a lanthanum cobaltate-biochar-based composite catalytic material.
2. The use according to claim 1, characterized in that: In step S1, when the walnut shells are cleaned, deionized water is used to clean the walnut shells 2 to 3 times; And / or, during the drying process, the cleaned walnut shells are placed in a constant temperature drying oven and dried at 60-80° C. for 6-8 hours; And / or, when the walnut shell powder is sieved, the particle size is set to 60 meshes.
3. The use according to claim 1, characterized in that: In step S2, the concentrations of Co(NO3)2·6H2O, La(NO3)3·6H2O, and citric acid in the mixed solution are 30-40 mmol / L, 30-40 mmol / L, and 35 mmol / L, respectively.
4. The use according to claim 1, characterized in that: In step S2, the volume ratio of the added mass of the walnut shell powder to the mixed solution is 30 g / L to 60 g / L.
5. The use according to claim 1, characterized in that: In step S2, the stirring and mixing time at room temperature is 20 to 60 minutes.
6. The use according to claim 1, characterized in that: In step S2, the pH of the mixed solution is adjusted to 7-9 using aqueous ammonia, and then the mixed solution is stirred for 20-40 minutes until there is no obvious change in the color of the mixed solution, which indicates that the lanthanum cobaltate is completely precipitated.
7. The use according to claim 1, characterized in that: In step S3, the heating rate during the pyrolysis treatment is 3-5°C / min, the pyrolysis treatment temperature is 600-800°C, and the pyrolysis treatment time is 2-4 h.
8. The use according to claim 1, characterized in that: In step S3, during the pyrolysis process, high-purity nitrogen is used as the protective gas.
Citation Information
Patent Citations
Method for preparing rare earth perovskite / biochar composite material from forestry and agricultural residues and application of rare earth perovskite / biochar composite material
CN112604690A